(untitled) (Economics and region, 2025)
The article examines the labor factor as one of the key factors of economic development of socio-ecological-economic systems of all levels. Its driving forces of extensive and intensive nature that affect regional economic development are determined. The indicators of the specific weight of the working-age population, the size of the labor force, the employment rate of the population, the working time fund of one full-time employee (person-hours) are recognized as extensive. The indicators of labor force quality and labor productivity are recognized as intensive. The state of labor resources in the regions of Ukraine on the eve of a full-scale invasion of a neighboring country is analyzed. Negative trends in the labor sector were identified that developed by 2022 and intensified in the context of a large-scale military invasion of a neighboring country in 2022-2025.The high level of economic potential of industrial enterprises in the context of opportunities for creating added value is critically important for the national economy of Ukraine and budget formation at all levels, as well as the formation of the country’s export industrial potential. At the same time, the industrial sector of the economy traditionally employs qualified workers, who, unfortunately, are being dispersed during the protracted military aggression of a neighboring country against Ukrainian society.It is noted that the regions with the highest level of labor potential have become front-line and suffer the greatest losses under the influence of military operations. Attention is focused on the low level of labor productivity in Ukraine, achieved over the past twenty years, in comparison with neighboring states and states with experience of post-war reconstruction. It is noted that the deterioration of the demographic situation in Ukraine is one of the most critical consequences of the armed aggression of a neighboring country, the impact of which will be felt by all spheres of life of Ukrainian society for a long time. It is generally accepted that if most losses during hostilities are in human capital, then post-war recovery is slower than in cases where mainly physical capital is destroyed.